2019
DOI: 10.1111/1756-185x.13476
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen reverses nicotine‐induced inflammation in chondrocytes via reducing the degradation of ECM

Abstract: Problem: Osteoarthritis (OA) is a chronic disease with a very high incidence and the pathology of which is quite complex. Epidemiological investigation showed that OA may be related to smoking and estrogen levels, but there are few studies focused on the cross-effect of these two factors. This research aims to investigate the molecular mechanism of nicotine and estrogen effects on chondrocytes to study the effect of smoking on the incidence of osteoarthritis in women. Method of the study:Nicotine was added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…As the activity of ERa was stimulated by tamoxifen in mice, the expression of p-Smad2/3 (which are downstream transcription factors of TGF-b signaling pathway and essential in the progression of acquired and congenital HO) was decreased in a dose-dependent response to tamoxifen, following the overactive TGF-b signaling which was interrupted in the inflammation and chondrogenesis phases and subsequently the ectopic bone formation was retarded. This cross-regulation between ERa and TGF-b is consistent with a recent study of Peng et al [42]. It showed that estrogen has a potential inhibitory effect on TGF-b1 signaling pathway by reducing the expression of Smad2/3 after inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…As the activity of ERa was stimulated by tamoxifen in mice, the expression of p-Smad2/3 (which are downstream transcription factors of TGF-b signaling pathway and essential in the progression of acquired and congenital HO) was decreased in a dose-dependent response to tamoxifen, following the overactive TGF-b signaling which was interrupted in the inflammation and chondrogenesis phases and subsequently the ectopic bone formation was retarded. This cross-regulation between ERa and TGF-b is consistent with a recent study of Peng et al [42]. It showed that estrogen has a potential inhibitory effect on TGF-b1 signaling pathway by reducing the expression of Smad2/3 after inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…The estrogen was used to and the friction on the cell was measured. The μ and PRG4 content were both recovered a lot which indicates the protective effect of the estrogen on the lubrication as verified in this study and previously (Peng et al, 2019). There are seldom reports to state relation between estrogen and friction of the articular cartilage, though, the positive effect of the estrogen were studied through different pathway.…”
Section: Changes In Secretion Of Prg4 For Articular Cartilagesupporting
confidence: 88%
“…These results may be attributed to the expression levels of lubricants on the surface of the articular cartilage as evidenced by the immunohistochemistry results. After nicotine treatment, The level of inflammatory factors(TNF-α, IL-1β) was detected in our previous work (Peng et al, 2019). The increase in μ after nicotine treatment indicates a loss of the boundary lubricant, with PGR4 as the strongest candidate.…”
Section: Changes In Secretion Of Prg4 For Articular Cartilagementioning
confidence: 68%
See 1 more Smart Citation
“…Studies have shown that the decline in the level of estrogen in the body is closely related to the occurrence and severity of OA [ 3 ]. Studies have indicated that estrogen can reverse the degradation of the extracellular matrix caused by inflammation in chondrocytes [ 4 ]. Therefore, we believe that estrogen supplementation can alleviate the progression of OA.…”
Section: Introductionmentioning
confidence: 99%